PENGARUH ROA, TINGKAT INFLASI DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM - Selvi Yona Sari; Neni Sri wahyuni Nengsi; Desi Permata Sari; Anisa Tunaswara (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2019)
His study aims to analyze the effect of Return On Assets, Inflation Rate and Rupiah Exchange Rate on the share price of banking companies on the Indonesia Stock Exchange. Based on the results of the research processed for the variables Return on Assets, Inflation Rate and Rupiah Exchange Rate on Stock Prices shows the simultaneous and significant influence. This is shown in the results of hypothesis testing with F count. 36.99996> F table 3.06. With a significance of 0.000000 <0.05. The Return On Assets variable is partially negative and insignificant on the Stock Price. This is shown in the results of hypothesis testing with the number t count <t table that is 0.577606 <1.65566 with a significance value of 0.5647> 0.05. Variable Inflation Levels on Stock Prices show a positive and significant influence. This is shown in the results of hypothesis testing with a calculated number of 14.42283> t table 1.65566 with a significance value of 0.0000 <0.05. While the Rupiah Exchange Rate partially has a negative but significant effect on the Stock Price. This is shown in the results of hypothesis testing with the number t -12.45095 <t table 1.65566 with a significance value of 0.0000 <0.05.